Denying humanness to victims: How gang members justify violent behavior. (November 2014) - Alleyne, Emma; Fernandes, Isabel; Pritchard, Elizabeth
The high prevalence of violent offending amongst gang-involved youth has been established in the literature. Yet the underlying psychological mechanisms that enable youth to engage in such acts of violence remain unclear. One hundred eighty-nine young people were recruited from areas in London, UK, known for their gang activity. We found that gang members, in comparison to nongang youth, described the groups they belong to as having recognized leaders, specific rules and codes, initiation rituals, and special clothing. Gang members were also more likely than nongang youth to engage in violent behavior and endorse moral disengagement strategies (i.e., moral justification, euphemistic language, advantageous comparison, displacement of responsibility, attribution of blame, and dehumanization). Finally, we found that dehumanizing victims partially mediated the relationship between gang membership and violent behavior. These findings highlight the effects of groups at the individual level and an underlying psychological mechanism that explains, in part, how gang members engage in violence.